Children's narratives on migrant refugees: a practice of global citizenship (UCL Press, 2021)
Globalisation has brought about great social and economic impact, as well as great challenges. Major developments have taken place in the mobility of capital and, to a lesser extent, of goods; not so in the mobility of people seeking asylum due to persecution and war. This article approaches the phenomenon of migration, particularly of refugees, as learning content for early childhood. The research is presented from a qualitative approach based on the results of a project on this topic implemented in a rural school in Spain. The results of the data analysis reveal that children attribute external reasons, of survival, to the refugees' forced departure from their country of origin. The children's imaginary reproduces the social construction of adults on the status and situation of refugees, and they also show a critical attitude towards the violation of human rights and the abuse of fellow children. Finally, respect, cultural empathy and social commitment in the face of injustice are presented as fundamental values for education in global citizenship from the earliest stages of schooling.